2023
DOI: 10.1039/d2nj05491d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by steam reforming of methanol by Cu–Zn/CeAlO3 perovskite

Abstract: In steam reforming of methanol (SRM), the efficacy of CeAlO3 perovskite as support for a bimetal catalyst was investigated. The CeAlO3 perovskite was synthesized employing a mesoporous silica (MCF) hard...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…The only difference in the synthesis method was that the former included ammonium fluoride as part of the dissolution process; at least this differentiating factor resulted in a smaller surface area and a larger pore size (18.23 nm vs 17 nm). The results by Ranjekar et al [ 17 ] have nonetheless revealed a very strong 97.4% ethanol conversion and 82.1% H 2 selectivity at 400 °C due to the presence of smaller active metal particles (7.3 nm) embedded within the porous network. Widyaningrum et al [ 45,47 ] studied Ni/MCF‐S catalysts to generate H 2 from pyrolysis of cellulose, finding that the H 2 selectivity was much higher as compared to using SBA‐15 of Al 2 O 3 supports, as the calculated Brunauer–Emmett–Teller (BET) surface area of 825 m 2 g −1 and pore diameter of 17 nm were higher.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only difference in the synthesis method was that the former included ammonium fluoride as part of the dissolution process; at least this differentiating factor resulted in a smaller surface area and a larger pore size (18.23 nm vs 17 nm). The results by Ranjekar et al [ 17 ] have nonetheless revealed a very strong 97.4% ethanol conversion and 82.1% H 2 selectivity at 400 °C due to the presence of smaller active metal particles (7.3 nm) embedded within the porous network. Widyaningrum et al [ 45,47 ] studied Ni/MCF‐S catalysts to generate H 2 from pyrolysis of cellulose, finding that the H 2 selectivity was much higher as compared to using SBA‐15 of Al 2 O 3 supports, as the calculated Brunauer–Emmett–Teller (BET) surface area of 825 m 2 g −1 and pore diameter of 17 nm were higher.…”
Section: Introductionmentioning
confidence: 99%
“…These trends are generally in agreement with the findings of other researchers in the literature. [ 5,17 ] Furthermore, the CO generated could be subjected to the water–gas shift reaction (WGS), as shown in Equation () to generate even more H 2 . [ 16 ] Given the high‐temperature requirement to activate the reaction and the formation of carbonaceous products via C–C scission (such as via ethanol decomposition), these processes can expectedly favor sintering (i.e., metal particle compaction) and coke (i.e., solid carbon) formation to deactivate the Ni catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an active oxide, perovskite has characteristics that inert oxides (such as Al 2 O 3 ) do not have. Therefore, perovskite has unique advantages and potential as a metal oxide support 11 . Although supports do not directly show catalytic activity, they can affect the catalytic activity of copper catalysts supported on them 12 .…”
Section: Introductionmentioning
confidence: 99%
“… Due to varied reaction parameters and the composition of the catalysts involved, several reaction mechanisms have been hypothesized. We proposed in our prior work that the process starts with ethanol dehydrogenation to produce acetaldehyde, which is eventually converted to CH 4 and CO 2 .…”
Section: Introductionmentioning
confidence: 99%